2008
DOI: 10.1121/1.2935976
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intense neutron dose radiation on piezoceramics

Abstract: Four grades of commercial PZT materials have been exposed to nuclear radiation during five months in an irradiation channel of the BR1 research reactor at SCK•CEN (Belgium). This experimental study was performed in the framework of the Joint Instrumentation Laboratory with the CEA French Commission of Atomic Energy to validate these materials for future applications in severe conditions such as online measurements in irradiation experiments performed in research reactors. For this purpose, thin piezoelectric d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…The radiation effect on the sensitivity of piezoelectric transducer has been investigated and reported in several papers [27][28][29][30][31]. For high temperature and extended operation two approaches to design have been investigated: a) waveguide based transducer and b) fully immersion transducer.…”
Section: Introductionmentioning
confidence: 99%
“…The radiation effect on the sensitivity of piezoelectric transducer has been investigated and reported in several papers [27][28][29][30][31]. For high temperature and extended operation two approaches to design have been investigated: a) waveguide based transducer and b) fully immersion transducer.…”
Section: Introductionmentioning
confidence: 99%
“…Changes in both the mean frequencies and response up to 78% were reported. More recently, Augereau et al 94 has reported both gamma and neutron irradiations on piezoceramics, including neutron irradiations with a fluence of 1.6 x 10 21 n/cm 2 for 150 days. Although some irreversible effects were seen, variations in resonant frequency were less than 1%.…”
Section: New In-pile Instrumentation To Support Fuel Cycle Research Amentioning
confidence: 99%
“…Several studies, as indicated above, have examined the performance of PZT and other lead based piezoelectrics when exposed to radiation and high temperatures. 85,92,[94][95][96] The lead-based piezoelectric have relatively low Curie temperatures (~ 320°C / ~610°F). Manufacturers generally recommend a maximum operating temperature of half the Curie temperature (~160°C /~ 320°F).…”
Section: New In-pile Instrumentation To Support Fuel Cycle Research Amentioning
confidence: 99%
“…The proposed test temperature will be approximately 400 o C. It is proposed that the test exceed fast neutron fluences of prior piezoelectric transducer irradiations (e.g., > 1x10 21 n/cm 2 [25]). In order to observe rapid changes at relatively low fluences, it is proposed to start the test with the reactor slowly ascending to power.…”
Section: B Irradiation Conditionsmentioning
confidence: 99%